Awareness of clinical faculty about National Antibiotic Treatment Guidelines - Piryani, Rano Mal (Journal of Chitwan Medical College, 2018)
Ministry of Health and Population, Government of Nepal produced National Antibiotic Treatment Guidelines in 2014. With the objective to assess the awareness about national antibiotic treatment guidelines among the clinical faculty of Chitwan Medical College Teaching Hospital Bharatpur Nepal, a survey was conducted in January 2016 utilizing questionnaire contained demographic information and questions related to awareness. Out of 60 clinical faculty members, 39 (65%) participated; their age was 37.5±10.9 years, 87% were male. Only seven (17.95%) participants were aware of the guidelines; five among them even don’t know content. It seems that majority of the clinical faculty was not aware of national antibiotics treatment guidelines. This survey has its limitation as this is done only among clinical faculty of one tertiary care hospital. There is need of country wide survey on how these guidelines are being implemented as Nepal has to fulfill its commitment to achieve targets by 2020.